2020
DOI: 10.1016/j.jcv.2020.104590
|View full text |Cite
|
Sign up to set email alerts
|

Insights into immune evasion of human metapneumovirus: novel 180- and 111-nucleotide duplications within viral G gene throughout 2014-2017 seasons in Barcelona, Spain

Abstract: Highlights HMPV has a prevalence of 3%, affecting equally children and adults. 180- and 111-nucleotide duplications emerged, increasing in prevalence over seasons. G proteins w/ duplications protruded more from the membrane than w/o duplication. Viruses w/ duplications were more associated to LRTI in adults than w/o duplication. These facts suggest these duplications might enhance an immune evasion mechanism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
2
21
1
Order By: Relevance
“…These observations suggest the occurrence of independent duplication events that, ultimately, resulted in the establishment of a dominant variant leading to the emergence of the BA genotype. This is consistent with previous reports that indicate that more than one duplication event resulted in new variants of human metapneumovirus and RSV-A [34][35][36] .…”
Section: Discussionsupporting
confidence: 93%
“…These observations suggest the occurrence of independent duplication events that, ultimately, resulted in the establishment of a dominant variant leading to the emergence of the BA genotype. This is consistent with previous reports that indicate that more than one duplication event resulted in new variants of human metapneumovirus and RSV-A [34][35][36] .…”
Section: Discussionsupporting
confidence: 93%
“…A study in Italy identified only one A1 genotype virus among 49 children with HMPV infection, while Kong et al identified one case among 145 HMPV infections that were genotyped in China [ 37 , 38 ]. Many recent studies have failed to detect HMPV A1 cases indicating that this genotype might have become extinct [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The 180-nucleotide duplication in the G gene of HMPV was reported to be present in respiratory samples obtained in 2014 and onward in Japan and Spain [ 7 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have failed to detect HMPV A1 cases indicating that this genotype might have become extinct [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The 180-nucleotide duplication in the G gene of HMPV was reported to be present in respiratory samples obtained in 2014 and onward in Japan and Spain [ 7 , 16 ]. Subsequently, the 111-nucleotide duplication in the G gene of HMPV was reported by Saikusa et al in viruses detected in 2017 in Japan [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations